2013
DOI: 10.1016/j.str.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Sodium Ion Binding Site in the Allosteric Modulation of the A2A Adenosine G Protein-Coupled Receptor

Abstract: SUMMARY The function of G protein-coupled receptors (GPCRs) can be modulated by a number of endogenous allosteric molecules. In this study, we used molecular dynamics, radioligand binding and thermostability experiments to elucidate the role of the recently discovered sodium ion binding site in the allosteric modulation of the human A2A adenosine receptor, conserved among class A GPCRs. While the binding of antagonists and sodium ions to the receptor was non-competitive in nature, the binding of agonists and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
164
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 125 publications
(176 citation statements)
references
References 59 publications
9
164
3
Order By: Relevance
“…Most importantly, we learned that all mutations in the sodium ion binding pocket impact A 2A receptor signaling significantly, including both constitutive and agonist-stimulated activity. Although all mutant data in the present study are novel, we have shown a number of similar findings on the wild-type receptor before (Lane et al, 2012;Gutiérrez-de-Terán et al, 2013b), indicative of the robustness of the assay system. We will discuss our findings in the light of available mutation data in literature by examining the mutated amino acids individually.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Most importantly, we learned that all mutations in the sodium ion binding pocket impact A 2A receptor signaling significantly, including both constitutive and agonist-stimulated activity. Although all mutant data in the present study are novel, we have shown a number of similar findings on the wild-type receptor before (Lane et al, 2012;Gutiérrez-de-Terán et al, 2013b), indicative of the robustness of the assay system. We will discuss our findings in the light of available mutation data in literature by examining the mutated amino acids individually.…”
Section: Discussionsupporting
confidence: 67%
“…In the wild-type receptor, both ligands achieved an average number of four simultaneous hydrogen bonds, mainly with residues Asp52 2.50 and Trp246 6.48 [Supplemental Fig. 2;Gutiérrez-de-Terán et al (2013b)]. For amiloride, the number of hydrogen bonds dropped to approximately two in the two mutants examined, as well as for HMA with mutant W246…”
Section: Design Of Mutations In the Sodium Ion Bindingmentioning
confidence: 99%
See 3 more Smart Citations